2017
DOI: 10.1186/s12890-017-0437-z
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin for idiopathic acute exacerbation of idiopathic pulmonary fibrosis: a retrospective single-center study

Abstract: BackgroundAcute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) is a fatal condition without an established pharmaceutical treatment. Most patients are treated with high-dose corticosteroids and broad-spectrum antibiotics. Azithromycin is a macrolide with immunomodulatory activity and may be beneficial for treatment of acute lung injury. The objective of this study was to determine the effect of azithromycin on survival of patients with idiopathic AE of IPF.MethodsWe evaluated 85 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 24 publications
2
47
0
3
Order By: Relevance
“…An international working group in 2016 proposed to classify this complication into triggered (identified event: post-procedure, drug toxicity, infection, aspiration) or idiopathic (unidentified inciting event) acute exacerbation 36 . Recent data associating acute exacerbation with the lung microbiome and with the host immunosuppressive states, and retrospective studies showing the preventive effect of antibiotic therapy suggest the role of infection in the pathogenesis of acute exacerbation and progression of pulmonary fibrosis 7,[42][43][44][45] . Further, a double-blind, randomized, placebo-controlled study showing improvement of symptoms and exercise capacity in progressive IPF patients treated with co-trimoxazole, and a subsequent double-blind follow-up and multicenter study showing significant reduction of mortality with better quality of life and less respiratory tract infections in IPF patients treated with co-trimoxazole also support the pathogenic role of bacteria in lung fibrosis 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…An international working group in 2016 proposed to classify this complication into triggered (identified event: post-procedure, drug toxicity, infection, aspiration) or idiopathic (unidentified inciting event) acute exacerbation 36 . Recent data associating acute exacerbation with the lung microbiome and with the host immunosuppressive states, and retrospective studies showing the preventive effect of antibiotic therapy suggest the role of infection in the pathogenesis of acute exacerbation and progression of pulmonary fibrosis 7,[42][43][44][45] . Further, a double-blind, randomized, placebo-controlled study showing improvement of symptoms and exercise capacity in progressive IPF patients treated with co-trimoxazole, and a subsequent double-blind follow-up and multicenter study showing significant reduction of mortality with better quality of life and less respiratory tract infections in IPF patients treated with co-trimoxazole also support the pathogenic role of bacteria in lung fibrosis 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation also contributes to acute exacerbations in IPF [21]. In recent retrospective clinical observations, AZT reduced mortality in acute exacerbations and hospitalization rates of IPF patients [22,23]. In addition to antimicrobial effects, AZT might act on inflammation and thus reduce severity of acute exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been observed that augmented concentrations of certain strains of Streptococcus, in BAL samples from IPF patients, associate with increased NOD receptor signaling and poor outcomes [69]. The potential contribution of bacteria in IPF pathogenesis is also an attractive area of investigation for novel treatment approaches [70]. It should be mentioned that, in our analysis, "NOD-like receptor signaling pathway" is linked with "MAPK signaling pathway", a central molecular pathway of IPF.…”
Section: Discussionmentioning
confidence: 77%